Web Reasoning and Rule Systems 9th International Conference, RR 2015, Berlin, Germany, August 4-5, 2015, Proceedings. - ten Cate, Balder; Mileo, Alessandra; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 9th International Conference on Web Reasoning and Rule Systems, RR 2015, held in Berlin, Germany, in August 2015. The 5 full papers, 4 technical communications presented together with 4 invited talks were carefully reviewed and selected from 16 submissions. The scale and the heterogenous nature of web data poses many challenges, and turns basic tasks such as query answering and data transformations into complex reasoning problems. Rule-based systems have found many applications in this area. The RR conference welcomes original research from all areas of Web Reasoning and Rule Systems. Topics of particular interest are: answer set programming, complex events, datalog, description logics, event-condition-action rules, information extraction, and logic programming.
Truth is a Lie: Rules & Semantics from Crowd Perspectives -- The Herbrand Manifesto: Thinking Inside the Box -- Extending Datalog Intelligence -- Analysis and Debugging of Ontology-based Data Access Specifications -- An Ontology for Historical Research Documents -- Semantic Views of Homogeneous Unstructured Data -- Supportedly Stable Answer Sets for Logic Programs with Generalized Atoms -- Planning with Regression Analysis in Transaction Logic -- Web ontology representation and reasoning via fragments of set theory -- Allotment problem in travel industry: A solution based on ASP -- A Rule-based Framework for Creating Instance Data from OpenStreetMap -- Web Stream Reasoning in Practice: on the Expressivity vs. Scalability Tradeo -- A procedure for an Event-Condition-Transaction language.
Keywords: Computer science; Software engineering; Computers; Database management; Data mining; Information storage and retrieval; Computer Science; Information Systems Applications (incl. Internet).; Information Storage and Retrieval; Database Management; Data Mining and Knowledge Discovery; Software Engineering; Computation by Abstract Devices; Electronic books